Legal Analysis of Unguaranteed Loans and Agreements (Case Study: Illegal Online Loans) - Shokhikhah, Zilda Khilmatus; Nurhamid, Nurhamid; Arrum, Desi Arianing; Utama, Adhyaqza (Budapest International Research and Critics University, 2021)
The existence of technology has streamlined human life today, even in carrying out transactions can also be done easily. Such as borrowing funds quickly and easily through online loan services. However, the unsecured credit business carried out online actually causes many problems, both through mechanisms such as the absence of guarantees and letters of agreement to billing by terrorizing customers. This study uses a descriptive method with a qualitative approach which aims to find out how the law applies to unsecured loans. The result is that in Articles 1131 and 1132 of the Criminal Code, unsecured credit can be made when both people know each other and it is poured into an agreement to binding each other. Meanwhile, credit without a letter of agreement will cause problems in the billing mechanism that will not be following applicable legal procedures regulated in the Act and POJK.